Investigating student's perception towards the effectiveness of Quranic memorization methods and techniques at MRSM Ulul Albab, Malaysia - Mohamad Rasyidi Bin Ghazali (Kulliyyah of Education, International Islamic University Malaysia, 2018)
MARA Junior Science College of Ulul Albab or MRSM (Maktab Rendah Sains MA-RA) Ulul Albab is one of the educational institutions at the secondary level organized by Bahagian Pendidikan Menengah Mara (MARA secondary division). Until 2017, there are four MRSMs in Malaysia that was selected by MARA to become the MRSM Ulul Albab. Ulul Albab Program is a unique program. This program was integrated the sci-ence stream, religious subjects and memorizing al Quran program in one curriculum known as Ulul Albab program. Every student who are selected to join this program need to finish their memorization for 30 chapters of al Quran within three years' study. Even MARA had experienced this program for nine years. Every MRSM has not yet been fulfilled the aim of BPM MARA to produce the Hafiz and Hafizah within three years. In dealing with this problem, this study was conducted to assess student percep-tion towards memorizing al Quran methods and techniques in memorizing al- Quran. On the other hand, this study also aims at analyzing the common methods and tech-niques to choose by student in memorizing al Quran. The datum was collected from 300 respondents from three MRSM Ulul Albab. There are 100 questionnaires set was distributed for each selected MRSMs. As a descriptive study, the data that was collected from respondents was analyzed using the statistical tool in SPSS V.21 descriptively to get the frequency, percentage, mean score and standard deviation for each item on the survey form. The result of the study shows a positive perception towards the method and techniques implemented in Ulul Albab program. Based on the result of the study, student feels unsatisfying towards the time table management at their institution. The result of the study also indicates a few methods and techniques choose by student in memorizing al Quran. The result of the study shows that there are a few methods and technique that were less used by the student in memorizing al Quran. Hopefully, this research may benefit not only for students but for all Ulul Albab stakeholders to ensure the sustainability of this program in future.